2022
DOI: 10.3390/cells11152448
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of Noncoding RNAs in the Progression of Gastrointestinal Cancers and Health Disparities

Abstract: Annually, more than a million individuals are diagnosed with gastrointestinal (GI) cancers worldwide. With the advancements in radio- and chemotherapy and surgery, the survival rates for GI cancer patients have improved in recent years. However, the prognosis for advanced-stage GI cancers remains poor. Site-specific GI cancers share a few common risk factors; however, they are largely distinct in their etiologies and descriptive epidemiologic profiles. A large number of mutations or copy number changes associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 277 publications
0
2
0
Order By: Relevance
“…Research into RNA modification is currently being extensively studied, and has provided the basis for identifying biomarkers of early‐stage GC and the untapped potential of therapeutic drugs. Existing clinical research has shown that long noncoding RNA (lncRNA) or microRNA (miRNA) molecules have potent antineoplastic activities, and some have even shown significant effects in early human clinical trials 8 . LncRNAs can serve as oncogenes or tumor suppressors via different mechanisms, whereas also representing a potential drug target or therapeutic entity 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into RNA modification is currently being extensively studied, and has provided the basis for identifying biomarkers of early‐stage GC and the untapped potential of therapeutic drugs. Existing clinical research has shown that long noncoding RNA (lncRNA) or microRNA (miRNA) molecules have potent antineoplastic activities, and some have even shown significant effects in early human clinical trials 8 . LncRNAs can serve as oncogenes or tumor suppressors via different mechanisms, whereas also representing a potential drug target or therapeutic entity 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing clinical research has shown that long noncoding RNA (lncRNA) or microRNA (miRNA) molecules have potent antineoplastic activities, and some have even shown significant effects in early human clinical trials. 8 LncRNAs can serve as oncogenes or tumor suppressors via different mechanisms, whereas also representing a potential drug target or therapeutic entity. 9 It has been reported that many noncoding RNAs act on critical parts in GC-related signaling pathways, and therefore could be used as targets for tumor diagnosis and therapy.…”
mentioning
confidence: 99%